Design of a coffee bean dryer prototype based on the internet of things - Ardian Afandi; Masthura Masthura; Nazaruddin Nasution (Universitas Riau, 2024)
Coffee is one of the plants that is widely cultivated in tropical countries such as Indonesia. Coffee plantation commodities at least contribute a lot to the Indonesian economy, which creates foreign exchange, farmer income, industrial raw materials, employment, and regional development. This research aims to design coffee bean dryer equipment using a heater as a heating element instead of sunlight for the process of drying coffee beans. When the temperature has reached 60°C, the heater will turn off briefly, and if the set time has not expired, the heater will always be alive. If the humidity does not decrease, the fan will fail. In this research, using experimental research procedures where each measurement is used effectively by each sensor so that the measurement results of each sensor are accurate. From the test results, it can be concluded that the initial weight before drying was 1000 grams, while the weight after drying was 880 grams.